2014
DOI: 10.1111/bjh.12827
|View full text |Cite
|
Sign up to set email alerts
|

Gender, race and diet affect platelet function tests in normal subjects, contributing to a high rate of abnormal results

Abstract: Summary To assess sources of variability in platelet function tests in normal subjects, 64 healthy young adults were tested on 2–6 occasions at 2 week intervals using 4 methods: platelet aggregation (AGG) in platelet-rich plasma (PRP) in the Bio/Data PAP-4 Aggregometer (BD) and Chrono-Log Lumi-Aggregometer (CL); and AGG in whole blood (WB) in the CL and Multiplate Platelet Function Analyzer (MP), with ATP release (REL) in CL-PRP and CL-WB. Food and medication exposures were recorded prospectively for 2 weeks p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
3
35
1
Order By: Relevance
“…Interestingly, from the data analysis, the only difference concerning possible gender variability dealt with the concentration of PDGF, which was higher in males, independently of the platelet count. This result may be partially discordant with the data published by Gomez et al [43], but it is certainly consistent with Miller and colleagues [44], who pointed out that gender, diet, and test system affected the results of platelet function in healthy subjects. It is noteworthy that the values of PDGF-BB here described are quite similar to those reported previously [6], while the content of PDGF was respectively higher in serum [45] and lower in plasma [46] according to other studies.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, from the data analysis, the only difference concerning possible gender variability dealt with the concentration of PDGF, which was higher in males, independently of the platelet count. This result may be partially discordant with the data published by Gomez et al [43], but it is certainly consistent with Miller and colleagues [44], who pointed out that gender, diet, and test system affected the results of platelet function in healthy subjects. It is noteworthy that the values of PDGF-BB here described are quite similar to those reported previously [6], while the content of PDGF was respectively higher in serum [45] and lower in plasma [46] according to other studies.…”
Section: Discussionsupporting
confidence: 85%
“…Subjects were also asked to refrain from consumption of foods previously described to affect platelet function for at least 24 hours prior to each study visit. A list of these foods was provided to the subjects during recruitment, and included phenolic- and polyphenol-rich foods, such as, cocoa products, coffee, tea, wine, other grape products and other colourful fruits and vegetables (Holt, Heiss, Kelm, & Keen, 2012; Miller, Rice, Garrett, & Stein, 2014). Dietary compliance was confirmed via questioning of the individual participants upon their arrival to the facility.…”
Section: Methodsmentioning
confidence: 99%
“…This result was consistent with previous reports; caffeine inhibited platelet aggregation by up-regulating adenosine A 2A receptor, [19] and chronic coffee drinking decreased platelet aggregation. [20] For the influence of sex, previous studies in Caucasians reported that baseline platelet aggregation in females was higher than that in males, [21][22][23] whereas in a study conducted in a healthy Korean population CTs were reported to be significantly longer in females. [17] Although one possible reason for this inconsistency would be a race difference (Caucasian versus Asian), more studies will be needed to better understand the influence of sex on CT.…”
Section: Discussionmentioning
confidence: 96%
“…After first dosing on Day 8, blood samples were collected at 0 (predose), 1,2,3,4,6,8,10,12,13,14,15,16,18,20,22,24,36,48, and 72 hours for PK. In the case of PD, blood samples were collected at 0 hour (baseline) on Day 1 and 0 (predose), 3,6,8,10,12,15,18,20,22,24,36, 48 and 72 hours after first dosing on Day 8. Among the 40 subjects who participated in the study, 29 completed sampling, and their PD data up to 24 hours for the reference drug was used in this analysis.…”
Section: Study Design and Datamentioning
confidence: 99%